2021
DOI: 10.3390/ijerph181910128
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Infections among Dental Health Workers in Germany—14-Year Time Trends

Abstract: Dental health workers (DHW) are at increased risk of acquiring occupational infections. Due to various protective measures, it can be assumed that infections have decreased over the past 14 years. Secondary data from a German accident insurance company was analyzed in terms of reported and confirmed occupational diseases (OD) in DHW from 2006 to 2019. A total of 271 claims were reported, of which 112 were confirmed as OD, representing an average of eight per year. However, the number of claims and confirmed OD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In our study, most dental students have been fully vaccinated against COVID-19. COVID-19 represents an occupational risk for dentists [ 10 , 20 , 21 ]. Vaccination against COVID-19 significantly reduces morbidity and absenteeism among HCP [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, most dental students have been fully vaccinated against COVID-19. COVID-19 represents an occupational risk for dentists [ 10 , 20 , 21 ]. Vaccination against COVID-19 significantly reduces morbidity and absenteeism among HCP [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient use of personal protective equipment was also frequent [ 14 ]. However, the past three decades occupational infections of HCP have decreased substantially due to the hepatitis B vaccination but also due to implementation of preventive measures, including the evaluation and management of incidents of blood exposure [ 12 , 13 , 20 ]. University-based studies across the world indicate that the percentage of dental students who have completed their vaccination schedule against hepatitis B ranges from 9.4% to 97%, often in association with gaps in their knowledge and practices about blood-borne infections [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the best practices to maximize safety for patients and healthcare personnel, including dental staff in dental care facilities, is imperative. This is also crucial given the risk of exposure to several infectious diseases, including vaccine-preventable diseases such as tuberculosis and COVID-19 in the context of droplet production and aerosol-generating procedures [10][11][12][13][14]. Review of published evidence regarding the dynamics of air splatters in healthcare facilities indicates areas of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are very scarce published data on new technologies in dental care facilities. This is of very important, also given the increased risk of dental care personnel for contracting infectious diseases, including vaccine-preventable diseases such as hepatitis B, tuberculosis, and COVID-19, especially during droplet production and aerosol-generating procedures [10][11][12][13]. Indeed, a recent study using occupational data from the Canadian Occupational Information Network found that four dental occupations (dental hygienists and therapists, dental assistants, dentists, and denturists) ranked as the top four occupations with the highest exposure to workplace indicators that increase the risk of exposure to COVID-19 [14].…”
Section: Introductionmentioning
confidence: 99%
“…Cumulatively, these risks can generate anxiety. The COVID-19 pandemic has greatly increased dentists' infection-related fear, confusion and anxiety [9][10][11][12][13]. Ahmed et al [11] found out among dentists from 30 countries worldwide that psychological effects of the COVID 19 pandemic include fear of their family members' infection, anxiety, fear and economic anxiety.…”
Section: Introductionmentioning
confidence: 99%